Inovasi Pelayanan : Kotak Saran Dua Fungsi di Lapas Kelas IIB Tebing Tinggi - Ferdy Ardiansyah; Ade Cici Rohayati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Community Service Program (KKN) was implemented with the aim of improving service and security at the Class IIB Tebing Tinggi Correctional Institution (Lapas) through a simple yet functional innovation in the form of a two-function suggestion box. This suggestion box was designed with two separate channels to accommodate aspirations from two separate sections, namely Bimbingan Narapidana/Anak Didik and Security, to facilitate the delivery of input in a safe, structured, and confidential manner. The implementation method of the activity included initial observation, identification of needs, design and construction of the box, and the socialization stage of its use. The results of this activity showed an increase in inmate participation in providing constructive suggestions and the creation of a more open communication channel without disrupting security stability. This innovation is one form of real contribution of cadets in supporting bureaucratic reform and more humane guidance in the correctional environment.